(untitled) (Colombia Medica, 2006)
A patient of 53 years old consults repeatedly by symptoms of sickness, tachycardia, sensation of facial flush, reappearance of muscular pains, permanent sensation of which something was going to happen. The case of Ana is approached having as referring the biopsychosocial approach starting off of this context considers like somatic hypothesis of work one pathology determined by its familiar emotions, affection and relations, where somatic symptom emerges like result from the relational upheavals and the processes of communication altered or non progressive after the intervention from the disciplinary group, disappearance the tachycardia, was reduced I am annoying and the muscular spasms, she profit to redesign and to recreate new spaces moving symptoms trims in the pain and disease, finding rewarding things also thought did not improve the familiar relations in the different subsystems, maintaining the respect by individualization of their members and redefining clearly his communication systems, you limit, rolls and handling of emotions.